Sistem Informasi Pemesanan Makanan Berbasis Client Server di Kopi We Salatiga - Narendra Basral Naseri; Nurgiyatna Nurgiyatna (Universitas Boyolali, 2021)
Many entrepreneurs have formed businesses in the culinary field. At this time, there are many restaurants not use computerization in making transactions. With limited human resources and lack of time effectiveness to serve customers who place orders, a food ordering information system is needed that can solve these problems. This system makes it easy to order food and manage the income, because when making transactions with customers you don't need to write menus manually and customers can get accurate info. This system, customers immediately know the details of him transaction. This study uses the Waterfall methodology then built with the Codeigniter’s framework and as a database support using MySQL. The data collection stage in making this information system is carried out by observation and interview. The system is implemented with a client server network architecture using a personal computer at the cashier as a server, so the system runs without internet access. The results of this system include ordering menus, processing order and transactions data, and printing transaction receipts in PDF. System testing using Black Box testing method, shows that the system has run well without any errors. Meanwhile, the results of questionnaire testing of 31 respondents, consisting of 30 visitors getting an interpretation percentage of 96% and 1 coffee shop owner getting 80% of the interpretation percentage. So, it can be concluded that the system is considered feasible to be applied and facilitates the process of ordering food.